PENGARUH MOTIVASI KERJA, SIKAP KERJA DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DAERAH KABUPATEN LABUHANBATU SELATAN - Lia Ulfayani; Sumardi .; Yance Irawan Nasution; Yemki Satria; Herinov Helfi (Manajemen dan Bisnis, 2021)
Problem of this study how influence of job motivation on performance. How influence of    work attitude on performance. How influence of  transformational leadership on  performance. How influence job motivation,    work attitude and  transformational leadership on   performance. The purpose of this study to determine and analyze the effect of  job motivation on   performance. Determine and analyze the effect of   work attitude on   performance. Determine and analyze the effect of  transformational leadership on   performance. Determine and analyze the effect of  job motivation,  work attitude and  transformational leadership on   performance.  Sample in the study is 36 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate job motivation variable has a positive and significant effect on performance.  work attitude variable has a positive and significant effect on   performance.  transformational leadership variable has a positive and significant effect on performance. Job motivation,  work attitude and  transformational leadership variable has a positive and significant effect on   performance.